IDENTIFIKASI GUGUS FUNGSI DARI SENYAWA METABOLIT SEKUNDER EKSTRAK ETANOL DAUN KAYU JAWA Lannea coromandelica - Sahribulan Sahribulan; Halifah Pagarra (Binomial, 2022)
Lannea Coromandelica is a plant that is widely used as a traditional medicinal plant. The Javanese wood plant Lannea Coromandelica is known to contain secondary metabolites in the form of alkaloids, flavonoids, saponins, and tannins. The aim of this study was to identify the functional groups of secondary metabolites of the Javanese wood leaf extract Lannea coromandelica. The method used is by extracting the Javanese leaves of Lannea coromandelica using 96% ethanol solvent and then identifying the functional groups of secondary metabolites using the FTIR (Fourier Transform Infrared) instrumentation. Identification results with FTIR showed absorption at wave number (cm-1) : 3424.39, 2919.45, 2850.72, 1626.59, 1561.39, 1441.97, 1377.81, 1232.30, 1100.41 there is an -O-H group, a C-O carbonyl group, an aromatic C=C ring, and a span of two. C-H and C-N groups which identify the presence of alkaloid compounds, saponins, flavonoids and tannins which are known as secondary metabolites from Javanese wood leaves Lannea coromandelica.